2016
DOI: 10.1515/pjfns-2015-0043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Encapsulated Fish Oil by Polymerized Whey Protein on the Textural and Sensory Characteristics of Low-Fat Yogurt

Abstract: Five types of polymerized whey protein (PWP1, PWP2, PWP3, PWP4 and PWP5) containing different amounts of fi sh oil were added to low-fat yogurt as fat replacers. The texture, apparent viscosity, and sensory properties of the yogurts were analyzed in comparison with full-fat ( 3.0%, w/w, fat) and low-fat (1.5%, w/w; and 1.2%, w/w) milk yogurt controls. The majority (~85%) of the particle size distribution was in the range of 1106±158 nm. Thermal property analysis indicated PWP was thermally stable between 50 o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…This could be explained by the larger complex formed by the interaction between PWP and casein micelles [33]. A similar result was reported where encapsulated fish oil with PWP samples could improve the viscosity of yogurt [23]. After the cooling oscillation measurement, the apparent viscosity of groups A to G is presented in Figure 3.…”
Section: Rheological Properties Of Yogurt During Fermentationsupporting
confidence: 80%
See 1 more Smart Citation
“…This could be explained by the larger complex formed by the interaction between PWP and casein micelles [33]. A similar result was reported where encapsulated fish oil with PWP samples could improve the viscosity of yogurt [23]. After the cooling oscillation measurement, the apparent viscosity of groups A to G is presented in Figure 3.…”
Section: Rheological Properties Of Yogurt During Fermentationsupporting
confidence: 80%
“…It was reported that the use of PWPs for the microencapsulation of ginsenosides (GSs) effectively masked the bitter taste of fermented milk containing GS [22]. Furthermore, whether encapsulating fish oil with PWP could adequately cover the fishy flavor in yogurts was a question studied by Liu et al [23]. The PWP-based microencapsulation could effectively mask the bitter taste of tartary buckwheat flavonoids (TBFs) and improve the color of yogurts containing TBF [24].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the heat treatment conditions for the whey proteins in food processing, the common pH value in the food system was between 7.5 and 8.5 (Liu et al, ; Mleko & Foegeding, ; Wang, Zhang, Ahmad, Cheng, & Guo, ; Zhao, Gao, Wang, & Guo, ), the current research was focused on the protein content from 8 to 10%, pH from 7.5 to 8.5, heating temperature from 70 to 85 °C, and heating time from 5 to 20 min. WPC (8,000, 78.3% protein, wt/wt) (Hilmar Ingredients, Hilmar, CA) was reconstituted at different protein concentrations (8.0, 8.5, 9.0, 9.5, and 10%, wt/vol) and, then, stored at 4 °C for 12 hr for complete hydration.…”
Section: Methodsmentioning
confidence: 99%
“…To elevate the daily intake of PUFA and mask the undesirable sensory properties of fish oil, various encapsulation forms were developed for the delivery into yogurt. Micro- and double emulsions [ 64 , 65 ], nanoliposomes [ 66 ], and particles obtained by the coacervation method using gelatin/acacia gum or by the thermal polymerization of whey proteins were prepared [ 67 , 68 ]. The encapsulation protects unsaturated fatty acids from deterioration.…”
Section: Yogurt Fortification With Nano/microencapsulated Bioactive Ingredientsmentioning
confidence: 99%